International Conference on Eurasian Economies 2017 2017
DOI: 10.36880/c08.01835
|View full text |Cite
|
Sign up to set email alerts
|

Content Analyses on Mission Statements of the Commercial Banks in Kyrgyzstan

Abstract: The concept of mission is still popular both in academic environment and business practices. Mission statements have been accepted as an important part of the strategic management process for organizations of all types; be it public sector, not-for-profit, private, for profit, a multinational or a SME. This paper aims to study the content of mission statements of Top10 commercial banks in Kyrgyzstan. The main objective of this study is to identify whether the mission statements of commercial banks contain comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The analysis of Table 2 indicates that 56.4% of the companies omitted the SGP construct in their mission statements; that is, most were silent regarding the expectations for growth, profitability, and survival. This may be explained by the lack of concern about the effect of future events on organizational growth or the companies being more orientated toward the short term (Najimudinova, 2018). This omission percentage is higher than that of Mussoi et al (2011), who, for a sample of 140 publicly-traded Brazilian companies, identified that 42% did not disclose the SGP construct.…”
Section: Descriptive Analysis Of the Sgp Constructmentioning
confidence: 83%
See 1 more Smart Citation
“…The analysis of Table 2 indicates that 56.4% of the companies omitted the SGP construct in their mission statements; that is, most were silent regarding the expectations for growth, profitability, and survival. This may be explained by the lack of concern about the effect of future events on organizational growth or the companies being more orientated toward the short term (Najimudinova, 2018). This omission percentage is higher than that of Mussoi et al (2011), who, for a sample of 140 publicly-traded Brazilian companies, identified that 42% did not disclose the SGP construct.…”
Section: Descriptive Analysis Of the Sgp Constructmentioning
confidence: 83%
“…The absence of the SGP construct in a mission statement indicates little strategic concern about the company's continuity, future, and growth (Najimudinova, 2018). Moreover, the lack of will to maximize profit and/ or minimize possible losses (Demsetz, 1997) may be sufficient reason for not mentioning the construct.…”
Section: The Sgp Constructmentioning
confidence: 99%